Outcomes and Predictors of Revision Labiaplasty and Clitoroplasty after Gender-Affirming Genital Surgery. Issue 6 (December 2019) - Boas, Samuel R.; Ascha, Mona; Morrison, Shane D.; Massie, Jonathan P.; Nolan, Ian T.; Shen, Jacson K.; Vyas, Krishna S.; Satterwhite, Thomas
Abstract : Background: Penile inversion vaginoplasty is the most common gender-affirming procedure for transfeminine patients. Patients undergoing this procedure may require revision labiaplasty and clitoroplasty. This study describes complications and outcomes from the largest reported cohort in the United States to undergo penile inversion vaginoplasty with subsequent revision labiaplasty and/or clitoroplasty. Methods: A retrospective chart review was performed of a single surgeon's experience with penile inversion vaginoplasty with or without revision labiaplasty and/or clitoroplasty between July of 2014 and June of 2016 in a cohort of gender-diverse patients assigned male at birth. Patient demographic data, complications, and quality of life data were collected. Univariate and multivariate comparisons were completed. Results: A total of 117 patients underwent penile inversion vaginoplasty. Of these, 28 patients (23.9 percent) underwent revision labiaplasty and/or clitoroplasty, with nine patients (7.7 percent) undergoing both procedures. Patients who underwent penile inversion vaginoplasty necessitating revision were significantly more likely to have granulation tissue ( p = 0.006), intravaginal scarring ( p < 0.001), and complete vaginal stenosis ( p = 0.008). The majority of patients who underwent revision labiaplasty and/or clitoroplasty reported satisfaction with their final surgical outcome (82.4 percent) and resolution of their genital-related dysphoria (76.5 percent). Conclusions: Patients who developed minor postoperative complications following penile inversion vaginoplasty were more likely to require revision surgery to address functional and aesthetic concerns. Patients responded with high levels of satisfaction following revision procedures, with the majority of patients reporting resolution of genital-related dysphoria. Transfeminine patients who undergo penile inversion vaginoplasty should be counseled on the possibility of revisions during their postoperative course. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.